Combined Papillary Renal Cell Carcinoma with Neuroendocrine Differentiation and Mucinous Tubular and Spindle Cell Carcinoma. (31st December 2018) - Wang, Gang; Yuan, Ren; Tucker, Tracy; Gates, Allan B.; Bellamy, Christopher D.; Hayes, Malcolm M.
Abstract : A unique case of combined papillary renal cell carcinoma (PRCC) and mucinous tubular and spindle cell carcinoma (MTSCC) presenting in a man aged 67 years is reported. The two separate components were distinct on morphological, immunohistochemical (IHC), and genetic grounds, while type 2 PRCC predominated. Three years after the initial diagnosis, the PRCC component metastasized to the lungs where it morphologically mimicked a pulmonary neuroendocrine tumor. Retrospectively focal neuroendocrine differentiation was demonstrated by IHC in the PRCC component of the primary neoplasm.